Disorder, low-energy excitations, and topology in the Kitaev spin-liquid - Meireles, Vítor Dantas (2022)
Frustrated magnetism is a very active research topic in condensed matter physics. The competition between different ground states often leads to a suppression of the ordering temperature and opens up the possibility that novel states emerge. One state of particular interest are the spin liquids, for which we find no broken symmetry down to T —› 0, where T is the temperature. Moreover, theses states show topological order and are notable for their peculiar features, such as long-range entanglement and the emergence of fractionalized excitations. The Kitaev model is a fascinating example of an exactly solvable model displaying a spin-liquid ground state in two dimensions. In real materials, however, deviations from the original Kitaev model are expected to appear, and we discuss relevant perturbations here. In this work, we investigate the fate of Kitaevs spin-liquid in the presence of disorder bond defects or vacancies for an extended version of the model. Considering static flux backgrounds, we observe a power-law divergence in the low-energy limit of the density of states, with a non-universal exponent. We link this power-law distribution of energy scales to weakly coupled droplets inside the bulk, in an uncanny similarity to the Griffiths phase often present in the vicinity of disordered quantum phase transitions. If time-reversal symmetry is broken, we find that power-law singularities are tied to the destruction of the topological phase of the Kitaev model in the presence of bond disorder alone. For weak to moderate site dilution, there is a transition from this topologically trivial phase with power-law singularities to a topologically non-trivial one. Therefore, diluted Kitaev materials are potential candidates to host Kitaevs chiral spin-liquid phase.